Quadruple coaxial catheter system on transvenous embolization for dural arteriovenous fistula. (April 2015) - Hayashi, Kentaro; Horie, Nobutaka; Morofuji, Yoichi; Fukuda, Shuji; Yamaguchi, Susumu; Morikawa, Minoru
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Although transvenous embolization (TVE) is an effective method for treating dural arteriovenous fistula (AVF), directing the catheter to the lesion site is difficult. Objective: We report on the utility of a quadruple coaxial catheter system for TVE. Materials and methods: The quadruple catheter system comprised a 6 Fr guiding sheath, 6 Fr guiding catheter, 4 Fr intermediate catheter, and a regular microcatheter. The system was utilized in 27 consecutive dural AVF cases treated with TVE. In this study, we reviewed our experience with this system, including the theory, method of use, and complications. Results: Stenosis or obstruction of the vascular access was identified in 12 cases. The catheter could not reach to the lesion in three cases of cavernous sinus (7·4%); therefore, transarterial embolization was employed. Angiographic results revealed that the cases consist of total occlusion (n = 16, 59·5%), subtotal (n = 10, 37·0%), and partial occlusion (n = 1, 3·7%). Complete resolution or improvement of symptoms was observed in 23 patients (85·2%), no improvement of symptoms was observed in three patients (7·4%), and deterioration of symptoms was observed in one patient (3·7%). Venous perforation occurred in one patient without any neurological deficit. The catheter system provided access to the lesion and provided stability during the mechanically demanding process navigating the catheter and placing the coils. Conclusion: We determined that the quadruple coaxial system was safe and efficient for TVE for dural AVF.